1998
DOI: 10.1073/pnas.95.12.7145
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal coincidence detection by voltage-sensitive electrical synapses

Abstract: Coincidence detection is important for functions as diverse as Hebbian learning, binaural localization, and visual attention. We show here that extremely precise coincidence detection is a natural consequence of the normal function of rectifying electrical synapses. Such synapses open to bidirectional current f low when presynaptic cells depolarize relative to their postsynaptic targets and remain open until well after completion of presynaptic spikes. When multiple input neurons fire simultaneously, the synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…In a typical adult crayfish antennule that is 2.5 cm long, and assuming a mean axonal conduction velocity of 3 m/sec, differences in spike arrival time at the brain (an additional 1-cm long pathway proximal to the flagellar bases) from sensilla at the base of a flagellum and from those near the tip could be as large as 8.5 msec. This latency difference could obviate coincident spike arrival and compromise the kind of electrical interactions between central afferent terminals that are so important for activation of the lateral giant system (11,12). Interestingly, however, we found that response latencies of spikes generated from sensilla near the tip of the antennular flagella and those generated near the flagellar base differ only by 1.0-1.5 msec recorded at the base.…”
Section: Resultsmentioning
confidence: 40%
See 2 more Smart Citations
“…In a typical adult crayfish antennule that is 2.5 cm long, and assuming a mean axonal conduction velocity of 3 m/sec, differences in spike arrival time at the brain (an additional 1-cm long pathway proximal to the flagellar bases) from sensilla at the base of a flagellum and from those near the tip could be as large as 8.5 msec. This latency difference could obviate coincident spike arrival and compromise the kind of electrical interactions between central afferent terminals that are so important for activation of the lateral giant system (11,12). Interestingly, however, we found that response latencies of spikes generated from sensilla near the tip of the antennular flagella and those generated near the flagellar base differ only by 1.0-1.5 msec recorded at the base.…”
Section: Resultsmentioning
confidence: 40%
“…The neurophysiological substrates of startle behaviors include interneuron axons of very large diameters that conduct impulses rapidly to excite relevant efferent pathways (1)(2)(3)(4)(5) and electrical synapses in the sensory-afferent pathways that trigger the interneurons and, in some systems, the motor neurons involved in the behavior (6). One of the startle behaviors that has been most intensively studied is a tailflip reflex initiated by one of the two sets of these high-speed interneurons-the lateral giant fibers-in the ventral nerve cord of crayfish (7)(8)(9)(10)(11)(12). Rectifying electrical synapses between sensory-afferent terminals and the lateral giant fibers and between large tactile interneurons and the lateral giants, passes current directly into these paired axons and, when several afferent terminals fire simultaneously, they sum effectively to produce enhanced excitatory postsynaptic potentials in their targets (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory-and S-cells all excite the L-motoneurons (Muller, 1979). Although the S-cell differs from other giant axons because it is not itself able to generate significant shortening of the animal (Gardner-Medwin et al, 1973), input to the L-motoneuron from the S-cell coincident with sensory-cell input may enhance the motoneuron's response, similar to an effect observed in the crayfish escape circuit (Edwards et al, 1998). Thereby, the S-cell may strengthen shortening during sensitization.…”
Section: Physiological and Behavioral Significancementioning
confidence: 85%
“…voltage dependent) gap junctions (e.g. Edwards, Heitler, Leise, & Friscke, 1991;Edwards, Yeh, & Krasne, 1998). BEATS filling-in is now introduced formally, with parameter values given in Table 2.…”
Section: Beats ('Bigger Eats Smaller') Filling-inmentioning
confidence: 99%